Acute Pulmonary Edema After Double Mechanical Valve Replacement - Audrey Poulat, MD; Constance Verdonk, PhD; Marylou Para, PhD; Ali Jendoubi, MD; Takoua Khzouri, MD; Jean Nicolas Senemaud, PhD; Yves Castier, PhD; Rainu Richaud, MD; Phalla Ou, PhD; Bernard Iung, PhD; Patrick Nataf, PhD (JACC: Case Reports, 2024)
We report a case of a 16-year-old man in cardiogenic shock secondary to On-X mitral prosthesis dysfunction due to leaflet embolization through aortic mechanical prosthesis. He underwent an emergency redo mitral valve replacement and, a few days later, leaflet removal by open aortic surgery with full recovery.